In vitro plant regeneration and metabolite profiling of an aromatic medicinal plant Ruta graveolens L. by using GC-MS - Hussain, Malik Aabid; Nathar, Varsha Nitin; Mushtaq, Roohi (Current Botany, 2022)
Ruta graveolens L. is an endemic plant of the Mediterranean region. It has been used for centuries as a medical preparation and has a variety of roles because of its varied chemical composition. In vitro culture is a useful tool for both multiplication and study of important secondary metabolites. The present study was aimed to develop an effective and reproducible protocol for callus induction and indirect plant regeneration of Ruta graveolens (L.) by using leaf explants and to analyze chemical components present in different extracts of Ruta graveolens. The leaf explants were cultured on MS medium augmented with different combinations and concentrations of auxins and cytokinins for callus induction, shoot multiplication and rooting. The optimum plant growth regulator concentration for callus induction, shoot multiplication and root formation was recorded in MSM+2,4-D(1.5mg/L)+NAA(1.5 mg/L), MSM+ BAP (1.5mg/L) +IBA (1.0 mg/L) and half strength MSM+IBA(0.50 mg/L) respectively. The rooted Plantlets were successfully acclimatized and established in earthen pots. The leaves, stem, roots and callus of Ruta graveolens were extracted by using Acetone and Ethyl acetate solvents followed by volatile compound analysis using GC-MS. The phytochemical assay showed that extracts of Ruta graveolens contain various phytoconstituents having potential bioactivity. The major compounds found were 1, 3-Dioxolane-4-propanol, 2, 2-Dimetheyl-, kokusaginine, Bergaptene, 2 Undecanone, 3-Hexene-2-one, Alpha, - 1- Arabinopyranose, 1, 2:3,4-bis-o, and 1- (1,3-Benzodioxol-5-ylmethyl)-3-Nitro-1 which might be primarily contributing in the biological activity of the plant. The results of this study will make a way for the production of herbal medicines for various ailments by using callus cultures of Ruta graveolens L.